Extratropical Factors Affecting the Variability in Summer Precipitation over the Yangtze River Basin, China - Li, Xinyu; Lu, Riyu (Journal of climate, 2017)
The Yangtze River basin (YRB), a typical East Asian monsoon region, experiences a large year-to-year variability in summer precipitation and is subject to both floods and droughts. There is a well-known seesaw relationship in precipitation between the tropical western North Pacific and the YRB, but more than half of the variance in precipitation in the YRB cannot be explained by this seesaw pattern. The authors therefore investigated other physical factors that might affect precipitation in the YRB. The results indicate that the northeasterly anomaly in the lower troposphere to the north of the YRB plays an important role in the variability in precipitation. This northeasterly anomaly is paired with the southwesterly anomaly to the south of the YRB. They both play an important role in water vapor accumulation over the YRB and intensify the meridional gradient of the equivalent potential temperature θₑ over the YRB by bringing dry and cool air from the north and wet air from the south. This intensified θₑ gradient favors convective instability and heavier rainfall in the YRB, as previous studies on mei-yu weather have indicated. Furthermore, it is found that the zonally oriented teleconnection along the Asian westerly jet and the meridional displacement of the jet can affect circulation in the lower troposphere and precipitation in the YRB. These results highlight the role of extratropical circulation anomalies and thus contribute to a more comprehensive understanding of the variability of precipitation in the YRB.